Comparative genomic and antimicrobial resistance profiles of Salmonella strains isolated from pork and human sources in Sichuan, China - Zuo, Haojiang; Yang, Yang; Su, Minchuan; Huang, Weifeng; Wang, Jian; Lei, Gaopeng; Kong, Ximei; Chen, Peng; Leng, Yun; Yuan, Qiwu; Zhao, Yuanyuan; Miao, Yanfang; et al. (Frontiers in Microbiology, 2025)
IntroductionSalmonella detection in retail pork is increasing, yet studies on its antimicrobial resistance (AMR) profiles and genomic characteristics remain limited. Moreover, it is still unclear whether certain Salmonella sequence types (STs) are consistently or rarely associated with pork as a transmission source. Sichuan province, the largest pork-production region in China, provides a critical setting to investigate these dynamics.MethodsIn this study, 213 Salmonella strains isolated from pork and human sources (2019–2021) underwent phenotypic AMR testing and whole-genome sequencing (WGS).ResultsResistance profiling revealed a higher prevalence of AMR in the pork-derived strains, particularly in veterinary-associated antibiotics. We identified STs not observed in pork in this study, such as ST23 (S. Oranienburg) and the poultry-commonly associated ST32 (S. Infantis), suggesting potential non-pork transmission routes for these Salmonella STs. To quantify sequence type diversity within each sample source, we introduced the sequencing type index (ST index = number of different STs/ total isolates). The ST index was 32% (49/153) for human-derived isolates and 20% (12/60) for pork-derived isolates. PERMANOVA analysis revealed significant differences in the structural composition of sequence types between human- and pork-derived isolates (p = 0.001), indicating that pork may harbor specific Salmonella STs more frequently.DiscussionThese findings highlight the role of pork as a reservoir for certain Salmonella STs, while also implying potential non-pork transmission pathways. The ST index represents a novel metric for assessing Salmonella diversity across different sample sources, offering a better understanding of genetic variation and transmission dynamics.